Selección de descriptores de tensión para localización de fallas en redes de distribución de energía - Mora Flórez, Juan José; Corrales C., Diego A.; Carrillo Caicedo, Gilberto (Ingeniería, 2005)
Permanent and transient power supply interruption affects power quality indexes related to continuity and causes negative effects in industry, commercial and residential users.As alternative to solve this problem,transmission networks have efficient fault location and protection schemes. Distribution facilities are constrained by technical,economical and operative aspects to implement fault identification and location strategies.In this paper an alternative solution of the fault location problem in power distribution systems, having a minimum of investment from utilities and giving appropriate information which helps to prevent and attend faults. By means of voltage signal characterization measured at the distribution substation and using an optimization and learning technique known as Support Vector Machines (SVM), the most probable zone where the fault was happened is located. The obtained results help to reduce time to locate faults in power distribution systems having a relatively low economical investment.